2016
DOI: 10.1111/jnu.12191
|View full text |Cite
|
Sign up to set email alerts
|

Dying Care Interventions in the Intensive Care Unit

Abstract: Assessment of nursing activities implemented in the care of dying patients in the ICU may help identify issues specific to nursing practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
(49 reference statements)
0
13
0
2
Order By: Relevance
“…Others (Powazki et al, ) also found that American ICU nurses perceived that they had the ability and knowledge to care physically and psychologically for their ICU patients at the end of life. On the other hand, nurses In the Czech Republic reported that they felt more confident delivering physical care but not psychological or social care (Kisvetrová et al, ) . These results conflict with our study as well as others where nurses reported a high quality of physical and spiritual care (Ho et al, ; Parish et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Others (Powazki et al, ) also found that American ICU nurses perceived that they had the ability and knowledge to care physically and psychologically for their ICU patients at the end of life. On the other hand, nurses In the Czech Republic reported that they felt more confident delivering physical care but not psychological or social care (Kisvetrová et al, ) . These results conflict with our study as well as others where nurses reported a high quality of physical and spiritual care (Ho et al, ; Parish et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Pflegende sind für Angehörige da, indem sie ihnen zuhören, offen für deren Äußerungen sind und als Ansprechpartner Präsenz zeigen [11][15] [16]. Sie fördern aber auch die Kommunikation innerhalb der Familie, indem sie anregen, sich untereinander über anfallende Entscheidungen auszutauschen [12].…”
Section: Familien Begleitenunclassified
“…Research on palliative care conducted in Australia on nurses (n = 25) shows that nurses have a passive role in providing care to patients with end life conditions, it because of nurses feel uncomfortable and less prepared (Bloomer, Endacott, O'Connor, & Cross, 2015 ) They also feels that they have a lack of role in providing care before death, nurses only do routine care (Bloomer et al, 2015). Giving counseling about death, offering food as patients' culture, and counseling on funeral planning are not well consulted by nurses (Kisvetrova, Skoloudik, Joanovic, Konecna, & Miksova, 2016). While, patients' need to obtain services, and respect dignity.…”
Section: Introductionmentioning
confidence: 99%